LEGAL PROTECTION OF CONSUMERS AGAINST PRICE FLUCTUATIONS OF STAPLE GOODS IN WEST NUSA TENGGARA PROVINCE - PUTRI, SUCI RAMADHANI (Research and Community Service Center of Akademi Bisnis Lombok, 2025)
This study examines the legal protection framework for consumers facing price fluctuations of staple goods in West Nusa Tenggara Province (NTB), Indonesia. Using a mixed-method approach combining quantitative price data analysis from BPS NTB 2024 and qualitative legal document review, this research evaluates the implementation of Law No. 8 of 1999 on Consumer Protection and Law No. 7 of 2014 on Trade. The findings reveal that while Indonesia possesses a robust normative legal framework for consumer protection, implementation at the regional level remains inadequate. Analysis of 2024 price data demonstrates significant fluctuations in strategic commodities: rice prices increased by 14% in March 2024, while shallot prices fluctuated up to 120% throughout the year. These variations indicate weak enforcement of price control mechanisms and insufficient application of fairness, balance, and legal certainty principles. The study concludes that strengthening regional regulations, enhanced inter-agency coordination, and improved market surveillance mechanisms are essential to ensure price affordability and protect consumers from predatory economic practices.